Molecular heterogeneity in complete cytogenetic responders after interferon-α therapy for chronic myelogenous leukemia: low levels of minimal residual disease are associated with continuing remission - Hochhaus, Andreas; Reiter, Andreas; Saußele, Susanne; Reichert, Anja; Emig, Michael; Kaeda, Jaspal; Schultheis, Beate; Berger, Ute; Shepherd, Patricia C. A.; Allan, Norman C.; Hehlmann, Rüdiger; Goldman, John M.; et al. (Blood, 2000)
A substantial minority of patients with chronic myelogenous leukemia (CML) achieve a complete response (CR) to treatment with interferon- (IFN), defined as the disappearance of Philadelphia chromosome-positive metaphases. Currently it is unclear how long IFN treatment should be continued for such patients. We used a competitive reverse transcriptase-polymerase chain reaction (RT-PCR) to quantify levels of BCR-ABL transcripts in 297 peripheral blood specimens collected from 54 patients who had achieved CR with IFN. The median duration of observation was 1.9 years (range, 0.3-11.0 years). Total ABL transcripts were quantified as internal control and results were expressed as the ratio BCR-ABL/ABL. All 54 patients had molecular evidence of residual disease, although 3 patients were intermittently PCR negative. The median BCR-ABL/ABL ratio at the time of maximal response for each patient was 0.045% (range, 0%-3.6%). During the period of observation 14 patients relapsed, 11 cytogenetically to chronic phase disease and 3 directly to blastic phase. The median ratio of BCR-ABL/ABL at maximal response was significantly higher in patients who relapsed than in those who remained in CR (0.49% versus 0.021%,P < 0.0001). Our findings show that the level of residual disease falls with time in complete responders to IFN, but molecular evidence of disease is rarely if ever eliminated. The actual level of minimal residual disease correlates with the probability of relapse. We suggest that for patients who reach CR, IFN should be continued at least until relatively low levels of residual leukemia are achieved. (Blood. 2000;95:62-66)
Gesehen am 13.04.2022